Global long-term trends in the total electron content - J. Urbář; J. Laštovička (Annales Geophysicae)
Total electron content (TEC) is an important parameter for ionospheric dynamics, global navigation satellite system/Global Positioning System (GNSS/GPS) signal propagation and related applications of GNSS/GPS signals. Despite this fact, the long-term trends in TEC have been studied only a little. Here, we analyze the JPL-35 (Jet Propulsion Laboratory-35) homogeneous series of global TEC data for 1994–2014 for selection of the optimum solar activity proxy for TEC analyses and the UPC (Universitat Politècnica de Catalunya) TEC data over 2003–2023 for estimating long-term trends in TEC. TEC trends are predominantly negative. TEC trends reveal a clear wavenumber 2 longitudinal structure in low/equatorial latitudes with strong negative trends in belts 0–60 and 180–240° E and weak trends in 90–150 and 270–330° E. For more detailed information on TEC trends, a longer series of reliable TEC data is required.